(untitled) ([USA], 2013)
Packed with real-world examples, this book illustrates the 12 principles of green chemistry. These diverse case studies demonstrate to scientists and students that beyond the theory, the challenges of green chemistry in pharmaceutical discovery and development remain an ongoing endeavor. By informing and welcoming additional practitioners to this mission, the negative environmental impact of pharmaceutical products will continue to be minimized. Green chemistry is the methodology by which chemical production in this industry can become more efficient, adding environmental stewardship to the noble mission of treating human disease.
Keywords: Biotechnology,Công nghệ sinh học